Mechanical response of tensegrity dissipative devices incorporating shape memory alloys. Issue 1 (November 2020) - Singh, N; Amendola, A; Santos, F; Benzoni, G; Fraternali, F
Abstract: To optimize the seismic performance prescribed by modern structural codes, buildings and infrastructures must provide adequate safety for design level earthquake excitations, with limited levels of damage. This paper deals with the computational modelling of a bracing system with tensegrity architecture, which operates as a lightweight mechanical amplifier of longitudinal displacements in the transverse direction, efficiently limiting the interstory drifts while dissipating energy. The proposed brace is based on a D-bar tensegrity structure with a rhomboidal shape comprising Shape-Memory Alloy (SMA) tendons. The SMA tendons can develop austenitic-martensitic (solid to solid) transformations, which enable them to amplify the signals into wide super elastic hysteresis, while subjected to mechanical cycles, comprising strains up to 6÷8%, with no residual deformations. The enhanced energy dissipation of the proposed SMA-D-bar (SMAD) braces are demonstrated through computational simulations of the response of braced frame to real earthquake events. The efficiency of the intended bracing to minimize the seismic impact of the served structure lays the foundation for the development of novel seismic energy dissipation systems integrating principles of tensegrity with superelasticity.